Thermal barrier ceramic material, preparation method thereof and thermal barrier coating material

By preparing thermal barrier ceramic materials with specific compositions, the problem of rapid failure of existing materials at high temperatures is solved, and high fracture toughness, phase stability and anti-sintering performance are improved. It is suitable for high-temperature environments such as scramjet engines and aerospace engines.

CN119859058APending Publication Date: 2025-04-22TSINGHUA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311359838.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing thermal barrier ceramic materials fail rapidly at temperatures of 1400°C or above, and lack materials with high fracture toughness, phase stability and sintering resistance.

Method used

By preparing a thermal barrier ceramic material composed of xA2O3·yBO2·zZrO2, where A is a trivalent rare earth metal ion and B is a tetravalent rare earth metal ion, including Hf4+, the total amount and type of rare earth doping elements are regulated, so that the material has a stable tetragonal phase and a partial cubic phase.

Benefits of technology

The phase stability and fracture toughness of thermal barrier ceramic materials are improved, with high melting point, low thermal conductivity and high thermal expansion coefficient, and can be used for a long time at higher temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859058A_ABST
    Figure CN119859058A_ABST
Patent Text Reader

Abstract

The invention provides a thermal barrier ceramic material, a preparation method of the thermal barrier ceramic material and a thermal barrier coating material, and the thermal barrier ceramic material comprises the following components: xA2O3.yBO2. ZZrO2, wherein A is a trivalent rare earth metal ion; b is a tetravalent rare earth metal ion, and B comprises Hf < 4 + >; the value range of x is 2%-4.9%; the value range of y is 1%-30%; 2x + y + z = 1; the thermal barrier ceramic material comprises a tetragonal phase structure and a cubic phase structure, and the content of the tetragonal phase structure is larger than that of the cubic phase structure. According to the thermal barrier ceramic material disclosed by the invention, ZrO2 is taken as a basis, and the thermal barrier ceramic material has a stable tetragonal phase and a part of cubic phase by regulating and controlling the total amount and types of rare earth doping elements, so that the high fracture toughness and excellent sintering resistance of the material are ensured while the phase stability is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of thermal barrier ceramic materials, and in particular to a thermal barrier ceramic material and a preparation method thereof, and a thermal barrier coating material. Background Art

[0002] In order to meet the ultra-high temperature protection requirements of scramjet engines, aerospace engines, and hot ends of high-temperature gas turbines, thermal barrier ceramics with excellent heat insulation and mechanical properties are usually used in the prior art to improve the operating temperature and working efficiency of the engine.

[0003] Traditional YSZ (7-8wt% Y2O3 partially stabilized ZrO2) ceramics have become the most widely used and mature thermal insulation and structural materials due to their excellent thermal and mechanical properties. However, when used at temperatures of 1400℃ and above, YSZ will rapidly undergo phase transformation and sintering, resulting in rapid material failure.

[0004] In response to the above problems, a lot of research has focused on finding new thermal insulation materials and structural materials with low thermal conductivity. However, whether it is rare earth zirconate or other new thermal protection materials, their fracture toughness is very low, which seriously reduces their service life. Therefore, finding thermal protection materials and structural materials with high fracture toughness, high phase stability and long-term use at higher temperatures (1400°C) has become the key. Summary of the invention

[0005] The embodiments of the present application provide a thermal barrier ceramic material and a preparation method thereof, and a thermal barrier coating material, which can improve the phase stability and fracture toughness of the thermal barrier ceramic, and at the same time have the advantages of high melting point, low thermal conductivity and high thermal expansion coefficient.

[0006] In a first aspect, an embodiment of the present application provides a thermal barrier ceramic material, which has the following composition: xA2O3·yBO2·zZrO2; wherein A is a trivalent rare earth metal ion; B is a tetravalent rare earth metal ion, and B includes Hf 4+ ; The value range of x is 2% to 4.9%; The value range of y is 1% to 30%; 2x+y+z=1; The thermal barrier ceramic material includes a tetragonal phase structure and a cubic phase structure, and the content of the tetragonal phase structure is greater than that of the cubic phase structure.

[0007] According to an embodiment of the first aspect of the present application, A includes Yb 3+ 、Lu 3+ Sc 3+ 、Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3 + , Y3+ 、Tm 3+ , Er 3+ At least one of .

[0008] According to an embodiment of the first aspect of the present application, the thermal barrier ceramic material has the following composition: aD2O3·bE2O3·yBO2·zZrO2; wherein D includes Yb 3+ 、Lu 3+ Sc 3+ At least one of; E includes Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3+ , Y 3+ 、Tm 3+ , Er 3+ At least one of the following; the value range of a is 1% to 4.9%; the value range of b is 0 to 1%; a+b=x.

[0009] According to an embodiment of the first aspect of the present application, B also includes Ce 4+ , based on the total value of y, Hf 4+ The content is 1%-60%.

[0010] According to an embodiment of the first aspect of the present application, based on the total amount of the phase structure as 100%, the content of the tetragonal phase structure is 55%-100%.

[0011] According to an embodiment of the first aspect of the present application, the thermal barrier ceramic material further includes a monoclinic phase, and the content of the monoclinic phase is less than 5% based on the total amount of the phase structure as 100%.

[0012] According to the embodiment of the first aspect of the present application, the fracture toughness K IC ≥4.0Mpam 1 / 2 .

[0013] In a second aspect, an embodiment of the present application provides a method for preparing a thermal barrier ceramic material, which is used for the thermal barrier ceramic material of the present application, and is characterized by comprising:

[0014] Providing raw material components, including xA2O3, yBO2 and zZrO2, x is in the range of 2% to 4.9%; y is in the range of 1% to 30%; 2x+y+z=1; wherein A is a trivalent rare earth metal ion; B is a tetravalent rare earth metal ion, and B includes Hf 4+ ;

[0015] mixing the raw material components to obtain a precursor mixture;

[0016] ball milling the precursor mixture and the solvent to obtain a mixed slurry;

[0017] The mixed slurry is subjected to solid-liquid separation to obtain a bulk material, and the bulk material is pre-calcined at least once to obtain a pre-fired thermal barrier ceramic material;

[0018] The pre-fired thermal barrier ceramic material is ball-milled, sieved, pre-pressed, and then calcined at 1350° C.-1600° C. for 6 h-10 h to obtain the thermal barrier ceramic material.

[0019] According to an embodiment of the first aspect of the present application, A includes Yb 3+ 、Lu 3+ Sc 3+ 、Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3 + , Y 3+ 、Tm 3+ , Er 3+ At least one of; and / or, B also includes Ce 4+ , based on the total value of y, Hf 4+ The content is 1%-60%.

[0020] In a third aspect, an embodiment of the present application provides a thermal barrier coating material, characterized in that it is formed by granulating and spraying the thermal barrier ceramic material of the present application.

[0021] Compared with the prior art, this application has at least the following beneficial effects:

[0022] In the embodiment of the present application, ZrO2 is used as the basis, and the total amount and type of rare earth doping elements are adjusted to make the thermal barrier ceramic material have a stable tetragonal phase and a partial cubic phase, while improving the phase stability, ensuring that the material has high fracture toughness and excellent sintering resistance. Among them, based on the total amount of material as 100%, the doping amount of trivalent rare earth metal oxide A2O3 in the thermal barrier ceramic material is 2%-4.9%, so that the thermal barrier ceramic material is mainly tetragonal phase, while improving the phase stability, ensuring that the material has high fracture toughness and low thermal conductivity, and the BO2 formed by the tetravalent rare earth metal ion B is similar to the ZrO2 lattice structure, which can improve the phase stability. The tetravalent rare earth metal ion B includes Hf 4+ The HfO2 crystal phase has a slow high temperature growth rate, which can improve the sintering resistance and fracture toughness. In addition, hafnium oxide HfO2 and ZrO2 are similar in chemistry and crystal structure, and HfO2 and ZrO2 are completely soluble in each other to form a solid solution, which helps phase stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.

[0024] Figure 1 It is the X-ray diffraction pattern of the thermal barrier ceramic material prepared in Examples 1 to 4 after being calcined at 1400° C. for 300 hours.

[0025] Figure 2 The following are scanning electron microscope photos of the blocks of Example 1 and Example 2. DETAILED DESCRIPTION

[0026] In order to make the application purpose, technical solution and beneficial technical effect of the present application clearer, the present application is further described in detail in conjunction with the embodiments below. It should be understood that the embodiments described in this specification are only for explaining the present application, not for limiting the present application.

[0027] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.

[0028] In the description of the present application, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number, and the “multiple” in “one or more” means two or more than two.

[0029] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0030] In a first aspect, an embodiment of the present application provides a thermal barrier ceramic material, which has the following composition: xA2O3·yBO2·zZrO2; wherein A is a trivalent rare earth metal ion; B is a tetravalent rare earth metal ion, and B includes Hf 4+; The value range of x is 2% to 4.9%; The value range of y is 1% to 30%; 2x+y+z=1; The thermal barrier ceramic material includes a tetragonal phase structure and a cubic phase structure, and the content of the tetragonal phase structure is greater than that of the cubic phase structure.

[0031] In the embodiment of the present application, the thermal barrier ceramic material is based on ZrO2. By adjusting the total amount and type of rare earth doping elements, the thermal barrier ceramic material has a stable tetragonal phase and a partial cubic phase. While improving the phase stability, it is ensured that the material has high fracture toughness and excellent sintering resistance.

[0032] Among them, based on the total amount of matter as 100%, the doping amount of trivalent rare earth metal ion oxide A2O3 in the thermal barrier ceramic material is 2%-4.9%, so that the thermal barrier ceramic material is mainly tetragonal phase, while improving the phase stability, ensuring that the material has high fracture toughness and low thermal conductivity, and the BO2 formed by the tetravalent rare earth metal ion B is similar to the ZrO2 lattice structure, which can improve the phase stability. The tetravalent rare earth metal ion B includes Hf, and the HfO2 crystal phase has a slow high-temperature growth rate, which can improve the sintering resistance and the fracture toughness. In addition, hafnium oxide HfO2 and ZrO2 are similar in chemistry and crystal structure, and HfO2 and ZrO2 are completely soluble in each other to form a solid solution, which is conducive to phase stability.

[0033] For example, the doping amount of the trivalent rare earth metal oxide A2O3 is 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8% or 4.9%. The doping amount of the tetravalent rare earth metal ion B is 1%, 2%, 3%, 4%, 5%, 6%, 10%, 15%, 20%, 25% or 30%.

[0034] In the present embodiment, the tetravalent rare earth metal ion B includes Hf 4+ , the tetravalent rare earth metal ions B can all be Hf 4 + , or it can be Hf 4+ And other tetravalent rare earth metal ions.

[0035] The fracture toughness in the present application is increased by 100% or more compared with new thermal protection materials such as rare earth zirconate ceramics; the material in the present application is calcined at 1400°C for 300 hours, and the monoclinic phase content is less than 5 mol%, indicating good phase stability; the excellent sintering resistance described in the present application means that the thermal barrier ceramic material obtained after sintering the doped ZrO2 green body has a higher porosity than the YSZ material.

[0036] The embodiments of the present application do not limit the aggregation state of the thermal barrier ceramic material, for example, it can be in block or powder form. The thermal barrier ceramic material of the embodiments of the present application can be used to prepare accessories of scramjet engines, aerospace engines, high-temperature gas turbines, etc. or used as a coating for accessories.

[0037] In some embodiments, the trivalent rare earth metal ion A comprises Yb 3+ 、Lu 3+ Sc 3+ 、Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3 + 、Dy 3+ , Y 3+ 、Tm 3+ , Er 3+ At least one of .

[0038] The trivalent rare earth metal ion A can be one ion, two ions, or more than two ions. For example, the trivalent rare earth metal ion A is Yb 3+ , or the trivalent rare earth metal ion A is Lu 3+ , or the trivalent rare earth metal ion A is Yb 3+ He Lu 3+ .

[0039] Among them, Yb 3+ 、Lu 3+ Sc 3+ The ionic radius of Nd is relatively small, which can improve the phase stability of thermal barrier ceramic materials. 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3+ , Y 3+ 、Tm 3+ , Er 3+ The ionic radius is relatively large, which can improve the sintering resistance of thermal barrier ceramic materials.

[0040] In some embodiments, the thermal barrier ceramic material has the following composition: aD2O3·bE2O3·yBO2·zZrO2; wherein D includes Yb 3+ 、Lu 3+ Sc 3+ At least one of; E includes Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy3+ , Y 3+ 、Tm 3+ , Er 3+ At least one of the following; the value range of a is 1% to 4.9%; the value range of b is 0 to 1%; a+b=x.

[0041] In the embodiments of the present application, trivalent rare earth oxides with relatively small ionic radius and relatively large ionic radius are mixed and doped, and the doping ratio of the two is regulated, so as to comprehensively improve the phase stability, thermodynamic properties and sintering resistance of the thermal barrier ceramic material.

[0042] Exemplarily, the value of a is 1%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8% or 4.9%.

[0043] In some embodiments, the tetravalent rare earth metal ion B further comprises Ce 4+ , based on the total value of y, Hf 4+ The content is 1%-60%.

[0044] In the present embodiment, the tetravalent rare earth metal ion B is Ce 4+ and Hf 4+ Thermal barrier ceramic materials include CeO2 and HfO2, Ce 4+ The ion radius is small, which has little effect on the phase structure of thermal barrier ceramic materials and can improve the stability performance. 4+ The thermal expansion coefficient of thermal barrier ceramic materials can be increased and the thermal conductivity can be reduced.

[0045] In some embodiments, based on the total amount of the phase structure being 100%, the content of the tetragonal phase structure is 55%-100%.

[0046] In the embodiment of the present application, by adjusting the total amount and type of rare earth doping elements, the thermal barrier ceramic material has a stable tetragonal phase and a partial cubic phase, which improves the phase stability while ensuring that the material has high fracture toughness and excellent sintering resistance. The content of the tetragonal phase structure is 55%-100%.

[0047] In some embodiments, the thermal barrier ceramic material further includes a monoclinic phase, and based on the total amount of the phase structure being 100%, the content of the monoclinic phase is less than 5%.

[0048] The thermal barrier ceramic material provided in the embodiment of the present application expands the zirconia-based material. By controlling the composition and proportion of the initial powder, it is ensured that the prepared material is mainly composed of tetragonal phase and a small amount of cubic phase. In addition, the monoclinic phase structure content of the thermal barrier ceramic material in the embodiment of the present application is less than 5 mol%, and has excellent phase stability.

[0049] In some embodiments, the fracture toughness K of the thermal barrier ceramic material IC ≥4.0Mpam 1 / 2 .

[0050] The thermal barrier ceramic material prepared in the embodiment of the present application has a very high fracture toughness K IC , its value exceeds 4.0MPam 1 / 2 .

[0051] In a second aspect, an embodiment of the present application provides a method for preparing a thermal barrier ceramic material, which is used to prepare the thermal barrier ceramic material in the embodiment of the first aspect, comprising:

[0052] Providing raw material components, including xA2O3, yBO2 and zZrO2, wherein the value range of x is 2% to 4.9%; the value range of y is 1% to 30%; 2x+y+z=1; wherein A is a trivalent rare earth metal ion; B is a tetravalent rare earth metal ion, and B includes Hf 4+ ;

[0053] mixing the raw material components to obtain a precursor mixture;

[0054] ball milling the precursor mixture and the solvent to obtain a mixed slurry;

[0055] The mixed slurry is subjected to solid-liquid separation to obtain a bulk material, and the bulk material is pre-calcined at least once to obtain a pre-fired thermal barrier ceramic material;

[0056] The pre-fired thermal barrier ceramic material is ball-milled, sieved, pre-pressed, and then calcined at 1350° C.-1600° C. for 6 h-10 h to obtain the thermal barrier ceramic material.

[0057] In the step of ball-milling the precursor mixture and the solvent to obtain a mixed slurry, zirconia balls and the precursor mixture can be ball-milled. For example, the ratio of the precursor mixture to the zirconia balls is between 1:20 and 1:10, and the ball-milling speed is between 200 and 300 rpm / min. The solvent can be alcohol or deionized water.

[0058] Before the step of mixing the raw material components to obtain the precursor mixture, the raw material components may be calcined to remove impurities such as water and carbon dioxide adsorbed by the raw material components. For example, the raw material components are calcined at 1100° C. for 1 h to 3 h.

[0059] In the step of obtaining a bulk material after solid-liquid separation of the mixed slurry, the bulk material can be obtained by filtering, and then the bulk material can be repeatedly ground, screened, and pre-calcined. The pre-calcination temperature is 1100°C-1250°C, and the time is 5h-10h. Through pre-calcination, the pre-fired thermal barrier ceramic material can have partial tetragonal and cubic phase products (description of structure or performance).

[0060] The step of ball-milling and sieving the pre-fired thermal barrier ceramic material and then pre-pressing and molding includes sieving the ball-milled powder, calcining at 1350-1500° C. for 1 h-3 h after spray granulation, and then sieving to select particles with a size of 30-110 microns. At this time, the particles with a size of 30-110 microns can be used for atmospheric plasma spraying. The pre-pressing molding can be processed by cold isostatic pressing.

[0061] By calcining at 1500℃-1600℃ for 6h-10h, a high-density thermal barrier ceramic material can be obtained, which can be used as EB-PVD target or as a high-temperature structural material.

[0062] The embodiment of the present application uses rare earth-doped zirconia with excellent thermodynamic properties and excellent phase stability as the target material, controls the overall content of rare earth oxides to ensure that the target material is mainly tetragonal phase with a small amount of cubic phase, and synthesizes the target material through a simple solid phase reaction.

[0063] Specifically, the preparation method of the thermal barrier ceramic material in the embodiment of the present application is based on ZrO2. By adjusting the total amount and type of rare earth doping elements, the thermal barrier ceramic material has a stable tetragonal phase and a partial cubic phase, and while improving the phase stability, the material is guaranteed to have high fracture toughness and excellent sintering resistance. Among them, based on the total amount of matter as 100%, the doping amount of trivalent rare earth metal oxide A2O3 in the thermal barrier ceramic material is 2%-4.9%, so that the thermal barrier ceramic material is mainly tetragonal phase, while improving the phase stability, the material is guaranteed to have high fracture toughness and low thermal conductivity, and the BO2 formed by the tetravalent rare earth metal ion B is similar to the ZrO2 lattice structure, which can improve the phase stability. The tetravalent rare earth metal ion B includes Hf, and the high temperature growth rate of the HfO2 crystal phase is slow, which can improve the sintering resistance and the fracture toughness. In addition, hafnium oxide HfO2 and ZrO2 are similar in chemistry and crystal structure, and HfO2 and ZrO2 are completely soluble in each other to form a solid solution, which helps phase stability.

[0064] The preparation method provided in the embodiment of the present application is simple, and the prepared thermal barrier ceramic material has a stable structure, excellent phase stability and is more resistant to sintering. After calcining at 1400° C. or above for 300 hours, it still has a stable composition and structure, and the monoclinic phase content is less than 5 mol%.

[0065] The fracture toughness of the thermal barrier ceramic material in the embodiment of the present application reaches 4.0 MPa 1 / 2 above.

[0066] The thermal barrier ceramic material provided in the embodiment of the present application has better sintering resistance than YSZ by doping HfO2, and the porosity of the green sample after sintering under the same conditions is higher than that of traditional YSZ.

[0067] In some embodiments, A includes Yb 3+ 、Lu 3+ Sc 3+ 、Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3+ , Y 3+ 、Tm 3+ , Er 3 + At least one of; and / or,

[0068] B also includes Ce 4+ , based on the total value of y, Hf 4+ The content is 1%-60%.

[0069] In a third aspect, an embodiment of the present application provides a thermal barrier coating material, which is formed by granulating and depositing the thermal barrier ceramic material of the first aspect of the present application.

[0070] Thermal barrier coating materials can be deposited by several techniques, including but not limited to thermal spraying (plasma spraying, flame spraying and HVOF spraying), sputtering and electron beam physical vapor deposition (EBPVD).

[0071] The thermal barrier coating material provided in the embodiment of the present application controls the composition and proportion of the initial powder to ensure that the prepared material is mainly composed of tetragonal phase and a small amount of cubic phase, and the monoclinic phase structure content of the thermal barrier ceramic material in the embodiment of the present application is less than 5 mol%, while improving the phase stability and ensuring that the material has high fracture toughness and excellent sintering resistance.

[0072] Example

[0073] The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations may be made within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0074] Example 1

[0075] (a) The raw material components are A2O3, CeO2, HfO2 and ZrO2, which are calcined at 1100°C for 1-3 hours to remove adsorbed impurities such as water and carbon dioxide;

[0076] (b) weighing the dried A2O3, CeO2, HfO2 and ZrO2 in a specific ratio, the contents of which are shown in Table 1;

[0077] (c) The weighed powders are mixed by ball milling, wherein the ball milling medium is zirconia balls and alcohol, and the ball milling time is 8 hours.

[0078] (d) separating the ball-milled slurry, grinding and sieving the obtained blocks, and then calcining at 1100° C.-1250° C. for 8 h;

[0079] (e) ball milling the obtained powder again for 7 hours, then sieving, and calcining at 1500° C.-1600° C. for 6-10 hours to obtain rare earth-doped ZrO2 powder;

[0080] (f) the powder after ball milling in step (e) is passed through a 200-300 mesh sieve, spray granulated, calcined at 1350-1500° C. for 1-3 hours, and then sieved to select particles with a size of 30-110 μm, which can be used for atmospheric plasma spraying;

[0081] (g) using a 15 mm diameter mold to pre-press the powder into a shape at a pressure of 5-10 kg; using cold isostatic pressing to hold the obtained green body at 200-300 MPa for 60-120 seconds;

[0082] (h) Finally, the sample is sintered at 1500-1600°C for 6-10 hours to obtain a high-density rare earth-doped ZrO2 bulk sample, which can be used as an EB-PVD target or as a high-temperature structural material.

[0083] Embodiments 2 to 4

[0084] The preparation process is similar to that of Example 1, except that the doping ratio of the rare earth oxide is different. The components of the thermal barrier ceramic materials of Examples 2 to 4 are shown in Table 1.

[0085] Comparative Example 1-2

[0086] The preparation process is similar to that of Example 1, except that the doping ratio of the rare earth oxide is different. The components of the thermal barrier ceramic materials of Comparative Examples 1 to 2 are shown in Table 1.

[0087] Comparative Example 3

[0088] The preparation process is similar to that of Example 1, except that in Comparative Example 3, yttrium oxide and niobium oxide are used as raw material components, and the ratio of the amount of yttrium oxide to niobium oxide is 1:1.

[0089] Comparative Example 3

[0090] The preparation process is similar to that of Example 1, except that in Comparative Example 4, ytterbium oxide and silicon oxide are used as raw material components, and the ratio of the amount of ytterbium oxide to silicon oxide is 1:2.

[0091] Comparative Example 4

[0092] The preparation process is similar to that of Example 1, except that in Comparative Example 4, the doping ratio of the trivalent rare earth oxide is 15 mol % and the doping ratio of the tetravalent rare earth oxide is 10 mol %.

[0093] According to national standards, the fracture toughness of the sample was measured by the three-point bending method. The size of the sample was 20 mm × 4 mm × 2 mm, and the wire cutting technology was used to pre-cut the incision. The incision depth was about 2 mm. The fracture toughness of the sample was measured using a universal testing machine. A total of 5 samples were tested. The test results are shown in Table 1.

[0094] The molar percentages of cubic phase, tetragonal phase and monoclinic phase were obtained by testing the XRD spectrum of the sample and performing peak separation.

[0095] Table 1 Fracture toughness and crystal structure of thermal barrier ceramic materials.

[0096]

[0097] Figure 1 The XRD patterns of the samples in Examples 1 to 4 before and after calcination at 1400°C for 300 hours are shown in FIG. Figure 1 It can be concluded that 0.01Gd2O3·0.03Lu2O3·0.1CeO2·0.1HfO2·0.72ZrO2, 0.03Lu2O3·0.05HfO2·0.15CeO2·0.74ZrO2, 0.015Lu2O3·0.01Yb2O3·0.15HfO2·0.15CeO2·0.65ZrO2 and 0.01Lu2O3·0.01Yb2O3·0.02ScO 1.5After the 0.1CeO2·0.05HfO2·0.79ZrO2 sample was calcined at 1400℃ for 300 hours, the material was mainly tetragonal phase, containing a small amount of cubic phase, and no monoclinic phase existed.

[0098] Figure 2 In the example 1, the sample ( Figure 2 b) and comparative YSZ samples ( Figure 2 a) SEM image after calcination at 1400 °C for 10 h. The results show that the new material sample has higher porosity and is more resistant to sintering.

[0099] Industrial Applicability

[0100] The doped ZrO2 material of the present application not only has high melting point, excellent sintering resistance, high strength and other properties, but also has a fracture toughness comparable to that of YSZ, which is significantly improved compared to new thermal protection materials or structural materials such as rare earth zirconates, and is 100% higher than pure rare earth zirconates, from ~2Mpam 1 / 2 Increased to ~4.0Mpam 1 / 2 Compared with traditional YSZ, it can be used for a long time at room temperature -2200℃. The above shows that this product has good practicality.

[0101] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A thermal barrier ceramic material, characterized in that: The thermal barrier ceramic material has the following composition: xA2O3·yBO2·zZrO2; Wherein, A is a trivalent rare earth metal ion; B is a tetravalent rare earth metal ion, and B includes Hf 4+ ; The value range of x is 2% to 4.9%; the value range of y is 1% to 30%; 2x+y+z=1; The thermal barrier ceramic material comprises a tetragonal phase structure and a cubic phase structure, and the content of the tetragonal phase structure is greater than that of the cubic phase structure.

2. The thermal barrier ceramic material according to claim 1, characterized in that: The A includes Yb 3+ 、Lu 3+ Sc 3+ 、Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3+ , Y 3+ 、Tm 3+ , Er 3+ At least one of .

3. The thermal barrier ceramic material according to claim 2, characterized in that: The thermal barrier ceramic material has the following composition: aD2O3·bE2O3·yBO2·zZrO2; Among them, D includes Yb 3+ 、Lu 3+ Sc 3+ At least one of; E includes Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3+ , Y 3+ 、Tm 3+ , Er 3+ At least one of; The value range of a is 1% to 4.9%; the value range of b is 0 to 1%; a+b=x.

4. The thermal barrier ceramic material according to any one of claims 1 to 3, characterized in that: Said B also includes Ce 4+ , based on the total value of y, Hf 4+ The content is 1%-60%.

5. The thermal barrier ceramic material according to claim 4, characterized in that: Taking the total amount of the phase structure as 100%, the content of the tetragonal phase structure is 55%-100%.

6. The thermal barrier ceramic material according to claim 1 or 5, characterized in that: The thermal barrier ceramic material further comprises a monoclinic phase, and the content of the monoclinic phase is less than 5% based on the total amount of the phase structure as 100%.

7. The thermal barrier ceramic material according to claim 1, characterized in that: The fracture toughness K of the thermal barrier ceramic material IC ≥4.0Mpam 1 / 2 .

8. A method for preparing a thermal barrier ceramic material, used for preparing the thermal barrier ceramic material according to any one of claims 1 to 7, characterized in that: include: Providing raw material components, including xA2O3, yBO2 and zZrO2, wherein the value range of x is 2% to 4.9%; the value range of y is 1 to 30; 2x+y+z=1; wherein A is a trivalent rare earth metal ion; B is a tetravalent rare earth metal ion, and B includes Hf 4+ ; mixing the raw material components to obtain a precursor mixture; ball-milling the precursor mixture and the solvent to obtain a mixed slurry; The mixed slurry is subjected to solid-liquid separation to obtain a block material, and the block material is pre-calcined at least once to obtain a pre-fired thermal barrier ceramic material; The pre-fired thermal barrier ceramic material is ball-milled, sieved, pre-pressed, and then calcined at 1350° C.-1600° C. for 6 h-10 h to obtain the thermal barrier ceramic material.

9. The method for preparing a thermal barrier ceramic material according to claim 8, characterized in that: A includes Yb 3+ 、Lu 3+ Sc 3+ 、Nd 3+ 、Eu 3+ 、Sm 3+ , Gd 3+ 、Ho 3+ 、Dy 3+ , Y 3+ 、Tm 3+ , Er 3+ At least one of; and / or, B also includes Ce 4+ , based on the total value of y, Hf 4+ The content is 1%-60%.

10. A thermal barrier coating material, characterized in that: The thermal barrier ceramic material according to any one of claims 1 to 7 is formed by granulating and spraying.